THE INFLUENCE OF WORK DISCIPLINE, SCHOOL CULTURE, AND PRINCIPAL'S LEADERSHIP ON TEACHER PERFORMANCE IN STATE ALIYAH MADRASAH IN MATARAM CITY - Ahsanu Amala, Lalu Muhammad; Prasojo, Lantip Diat (Universitas Islam Negeri (UIN) Sumatera Utara, 2025)
The study is intended to analyze the extent to which work discipline, school culture, and principal leadership impact teacher performance in Madrasah Aliyah in the Mataram City area. This study applied a quantitative approach with ex-post facto methods and surveys. This research used a survey strategy, using questionnaires as a data collection tool. The research population consisted of all teachers in three states and Aliyah Madrasah in Mataram City, totaling 169 people. The research sample was selected through probability sampling techniques, so that 114 teachers from the three MAs were selected. For the data collection process, the questionnaires had been validated both expertly and through empirical tests to support the accuracy of the research. Testing of the validity and reliability of the instrument was carried out with the help of SPSS Version 26 software. The test results show that, partially, work discipline has a positive and significant impact on teacher performance with a regression coefficient of 0.459. School culture shows a negative influence on teacher performance with a regression coefficient of -0.176. Meanwhile, the leadership of the principal also has a significant positive effect on teacher performance, with a regression coefficient of 0.498. Simultaneously, these three variables have a significant impact on teacher performance, with an F value of 98.026, which is greater than the F value in the table of 2.68. These findings confirm that the improvement of teacher performance is greatly impacted by the level of work discipline, the quality of the principal's leadership, and the supportive school culture conditions.